2016
DOI: 10.1007/978-1-4939-3023-4_64
|View full text |Cite|
|
Sign up to set email alerts
|

Characterizing Fluctuations of Arterial and Cerebral Tissue Oxygenation in Preterm Neonates by Means of Data Analysis Techniques for Nonlinear Dynamical Systems

Abstract: The cerebral autoregulatory state as well as fluctuations in arterial (SpO2) and cerebral tissue oxygen saturation (StO2) are potentially new relevant clinical parameters in preterm neonates. The aim of the present study was to test the investigative capabilities of data analysis techniques for nonlinear dynamical systems, looking at fluctuations and their interdependence. StO2, SpO2 and the heart rate (HR) were measured on four preterm neonates for several hours. The fractional tissue oxygenation extraction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For the resting-state dataset, we computed the channel-wise correlation as a metric to assess the global influence of expected spontaneous vascular and metabolic fluctuations that are present in both task and resting states 33 , 34 . As the primary analysis goal was to evaluate the presence of global fluctuations, we did not apply any further correction (e.g., principal component analysis 35 , 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…For the resting-state dataset, we computed the channel-wise correlation as a metric to assess the global influence of expected spontaneous vascular and metabolic fluctuations that are present in both task and resting states 33 , 34 . As the primary analysis goal was to evaluate the presence of global fluctuations, we did not apply any further correction (e.g., principal component analysis 35 , 36 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to consider that previous studies, mostly conducted in experimental settings, suggest that the neonatal sensor linearly correlates and reads ∼10% higher than the adult sensor. This information must be considered when analyzing cut-offs values for hypoxia and hyperoxia (21)(22)(23). The combination of low rScO 2 and abnormal electrocortical activity likely reflects decreased cerebral oxygen delivery or cerebral blood flow and should alert the clinician to the risk for brain injury.…”
Section: Physiologymentioning
confidence: 99%
“…The measurements were approved by the local ethics committee, and written informed consent was obtained from the parents before the study. The datasets used are the same as those analyzed by our previous study investigating another signal processing and data analysis framework [6].…”
Section: Subjects Instrumentation and Experimental Protocolmentioning
confidence: 99%
“…Long-term (i.e., several hours) monitoring of changes in SpO2 and StO2 offers insights into tissue oxygenation and the regulation of hemodynamics. In a previous study in preterm neonates [6] we found that the fluctuations in SpO2, SaO2, heart rate (HR) and fractional tissue-oxygen extraction, measured over several hours, showed properties (i.e. coupling of the signals and oscillations present) dependent on the individual subject.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation